LINGUOCULTUROLOGICAL FOUNDATIONS OF DISPUTE IN UZBEK AND ENGLISH COMMUNICATIVE BEHAVIOR (Scientific journal of the Fergana State University, 2026)
This article analyzes the linguocultural foundations of dispute behavior in Uzbek and English communicative cultures. A dispute, as a communicative act involving the exchange of opposing views, reflects the deep interaction between language and culture. The paper presents a comparative linguopragmatic analysis of how disputes are conducted in both cultures, focusing on strategies of expressing disagreement, politeness norms, face-saving techniques, and culturally influenced speech patterns. Authentic examples from real conversations, debates, and interviews in both languages are examined alongside qualitative data collected from native speakers. The study reveals that while English dispute culture emphasizes directness, critical reasoning, and individual opinion, Uzbek dispute culture prioritizes social harmony, respect, and indirect expression. These differences are rooted in broader cultural values and have significant implications for intercultural communication and language education.